ANALISIS PAKAR TERHADAP TINGKAT TURBULENSI LINGKUNGAN ORGANISASI BISNIS TELEKOMUNIKASI SELULAR DI INDONESIA - Dwi Idawati; Arya Hadi Dharmawan; Sjafri Mangkuprawira (Journal of Management and Business Review, 2012)
The key challenge for the telecommunication business industry in the global world’s is “assuring competitiveness and profitability” for their companies in turbulent environments. Never in history has the pace of change in the business environment been as rapid as it is now. Recent developments such as the global marketplace, customers’ demands that are differentiated by different buying power and product preferences in this environment, technological leadership is one of the key success factor. New technologies and new industries develop rapidly and customers are prepared to pay for the most newest technology. The company’s strengths and successful strategies of the corporate leadership in the past are likely to remain relevant in the future. The research findings revealed that the turbulent environment level in the mobile telecommunication industry was in the discontinuous –strategic level, where the future is not extension of the past. This environment situation facing by Indonesia’s telecomunication industry need the corporate leadership to challenge the organisation survival. This research is based on the qualitative descriptive method by using data obtained from telecommunication industry experts and secondary data.